2019
DOI: 10.1002/cpmb.86
|View full text |Cite
|
Sign up to set email alerts
|

Higher Mass Accuracy MALDI‐TOF/TOF Lipid Imaging of Human Brain Tissue in Alzheimer's Disease

Abstract: Matrix‐assisted laser desorption/ionization imaging mass spectrometry (MALDI‐IMS) is a well‐established technique for elucidating the location and relative abundance of a range of biomolecules. More recently, research into this technique has shifted from simple discovery and demonstration of utility to application in biomedical research. Here, we describe a protocol utilizing MALDI‐IMS for the spatial mapping of lipids in brain tissue from normal human brains and brains from patients with Alzheimer's disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…As MALDI TOF MSI measurements cannot be used for formal identification of the detected ions, the HMDB database was used to assign known biological entities to the m / z ratios (Tables S13–S16). The database search indicated that choline ( m / z = 104.1), phosphocholine ( m / z = 184.1), and glycerophosphocholine ( m / z = 258.1) could be detected in positive mode and that known cancer biomarkers such as lactate ( m / z = 89.1) and glutamine ( m / z = 145.1) could be detected in negative mode. , …”
Section: Resultsmentioning
confidence: 99%
“…As MALDI TOF MSI measurements cannot be used for formal identification of the detected ions, the HMDB database was used to assign known biological entities to the m / z ratios (Tables S13–S16). The database search indicated that choline ( m / z = 104.1), phosphocholine ( m / z = 184.1), and glycerophosphocholine ( m / z = 258.1) could be detected in positive mode and that known cancer biomarkers such as lactate ( m / z = 89.1) and glutamine ( m / z = 145.1) could be detected in negative mode. , …”
Section: Resultsmentioning
confidence: 99%
“…Lipid species play basic and vital roles in different physiological events as structural components of biological membrane, substance transport, energy storage, and intercellular signaling. , Mutations in the autosomal dominant genes encoding amyloid precursor protein (APP) and presenilins 1 and 2 (PS1 and PS2) lead to the subsequent accumulation of β-amyloid (Aβ) in the brain. The pathological accumulation and deposition of extracellular Aβ and aberrantly phosphorylated tau filaments in brain neurons finally lead to senile plaques and neurofibrillary tangles, consequently inducing the occurrence of Alzheimer’s disease (AD). Many studies based on MS imaging technique have demonstrated that AD is closely related to lipid change in the brain. …”
Section: Introductionmentioning
confidence: 99%
“…MS imaging techniques, including desorption electrospray ionization (DESI) and matrix assisted laser desorption ionization–mass spectrometry (MALDI-MS) imaging, have become a suitable and robust tool, which makes possible to profile distribution of endogenous lipids in the brain. Based on the above study, lipid features in space distribution in tissue slices of mouse brain could be described by DESI and MALDI-MS imaging techniques to reveal molecular pathologic changes. However, current studies are mainly focused on the pathological state of AD in the late stage. ,, Lipid alteration and its space distribution in mouse brain with early AD remain unknown. Based on the above knowledge, DESI and MALDI-MS imaging techniques can be used to visually uncover lipid dynamics in the brain of APP/PS1 mouse model (2 and 3 month old), which benefits in discovering biomarkers for the diagnosis of early-stage AD to acquire insight into early AD progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As moléculas irradiadas, adsorvem a energia e a transferem para as moléculas adicionadas com prótons, sendo os lipídeos as moléculas alvo neste estudo. Logo após, um captador detecta as variações de energia e a traduz, por meio de um software, para um gráfico [8].…”
Section: Introductionunclassified